Age trends in professional tennis players career: Are champions really precocious? - Maquirriain, J. (Medicine and Science in Tennis, 2009)
Background & Objective Top-ranked professional tennis players are usually young athletes. Their peak performance age has been previously studied (Schulz, R., 1988; Maquirriain, J., 1986 & 2005) but limited data exist on longitudinal age-related development of tennis players. The objective of this study was to explore the relationship between age and ranking position in male tennis players during their professional career. Material & Method Professional male players ranking during the last five years (2002-2006) were studied (www.atptennis.com). Subjects were divided in two groups according to their year-end ranking position: A=1-10; B=91-100. Their ranking position at the ages of 18, 21 and 24 year were determined and compared (t-test for independent samples). Conclusions. Results of this study confirmed previous data that age of peak performance of professional tennis players is 24 years old. The main finding of this study was that top-ten male tennis players ranked significantly higher than other successful players at ages of 18, 21 and 24 years. Analyzing the relationship between age and ranking position could help to identify potential tennis champions and monitor their development during the professional career.